Dexmedetomidine and Other Analgosedatives Alter Pupil Characteristics in Critically Ill Patients. (13th May 2022) - Chan, Wang Pong; Prescott, Brenton R.; Barra, Megan E.; Chung, David Y.; Kim, Ivy S.; Saglam, Hanife; Hutch, Meghan R.; Shin, Min; Zafar, Sahar F.; Benjamin, Emelia J.; Smirnakis, Stelios M.; Dupuis, Josée; et al.
Abstract : OBJECTIVES: In critically ill patients with neurologic disease, pupil examination abnormalities can signify evolving intracranial pathology. Analgesic and sedative medications (analgosedatives) target pupillary pathways, but it remains unknown how analgosedatives alter pupil findings in the clinical care setting. We assessed dexmedetomidine and other analgosedative associations with pupil reactivity and size in a heterogeneous cohort of critically ill patients with acute intracranial pathology. DESIGN: Retrospective cohort study. SETTING: Two neurologic ICUs between 2016 and 2018. PATIENTS: Critically ill adult patients with pupil measurements within 60 minutes of analgosedative administration. Patients with a history of intrinsic retinal pathology, extracranial injury, inaccessible brain imaging, or no Glasgow Coma Scale (GCS) data were excluded. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: We used mixed-effects linear regression accounting for intrapatient correlations and adjusting for sex, age, GCS score, radiographic mass effect, medication confounders, and ambient light. We tested the association between an initiation or increased IV infusion of dexmedetomidine and pupil reactivity (Neurologic Pupil Index [NPi]) and resting pupil size (mm) obtained using NeurOptics NPi—200 (NeurOptics, Irvine, CA) pupillometer. Of our 221 patients with 9, 897 pupil observations (median age, 60 [interquartile range, 50–68]; 59% male), 37 patients (166 pupil observations) were exposed to dexmedetomidine. Dexmedetomidine was associated with higher average NPi (β = 0.18 per 1 unit increase in rank-normalized NPi ± 0.04; p < 0.001) and smaller pupil size (β = –0.25 ± 0.05; p < 0.001). Exploratory analyses revealed that acetaminophen was associated with higher average NPi (β = 0.04 ± 0.02; p = 0.02) and that most IV infusion analgosedatives including propofol, fentanyl, and midazolam were associated with smaller pupil size. CONCLUSIONS: Dexmedetomidine is associated with higher pupil reactivity (high NPi) and smaller pupil size in a cohort of critically ill patients with neurologic injury. Familiarity with expected pupil changes following analgosedative administration is important for accurate interpretation of pupil examination findings, facilitating optimal management of patients with acute intracranial pathology.